Silica-aluminum cementing material concrete and preparation method thereof

By optimizing the ratio of silicon-aluminum gelling materials and adding steel fibers and water reducers, the problems of high cost and insufficient strength of traditional silicate cement concrete were solved, and a low-cost and high-strength silicon-aluminum gelling was prepared. Material concrete achieves efficient, economical and environmentally friendly concrete production.

CN119409472APending Publication Date: 2025-02-11CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411566289.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The production cost of traditional silicate cement concrete is high and has a great burden on the environment. At the same time, the strength of silicon-aluminum gelling material concrete is low, making it difficult to meet high strength requirements.

Method used

By optimizing the ratio of red mud, slag powder, cement and alkaline excitants, combined with the use of steel fibers and water reducers, a low-cost, high-strength silicon-aluminum gelling material concrete was prepared.

Benefits of technology

The compressive strength after 1 day of maintenance is >30.0MPa and the compressive strength after 28 days of maintenance in water is >60.0MPa, which has the advantages of fast strength formation and high final strength, while significantly reducing production costs and environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005119332360000161
    Figure BDA0005119332360000161
  • Figure BDA0005119332360000171
    Figure BDA0005119332360000171
Patent Text Reader

Abstract

The invention relates to the field of building materials, in particular to silicon-aluminum cementing material concrete and a preparation method thereof. The silicon-aluminum cementing material concrete comprises 100 to 200 parts of red mud, 0 to 100 parts of fly ash, 0 to 100 parts of steel slag, 0 to 100 parts of lithium slag, 100 to 300 parts of slag powder, 0 to 100 parts of cement, 0 to 50 parts of gypsum, 150 to 200 parts of water, 40 to 50 parts of an alkali activator, 10 to 40 parts of steel fiber, 700 to 750 parts of sand, 900 to 1200 parts of gravel and 1 to 5 parts of a water reducing agent. The water reducing agent comprises a naphthalene-based superplasticizer and calcium lignosulphonate; the cement comprises Portland cement and / or Portland cement clinker. The using amount of solid waste can reach 90%, the compressive strength of the concrete cured for 1 d is larger than 30.0 MPa, the compressive strength of the concrete cured in water for 28 d is larger than 60.0 MPa, and the concrete has the advantages of being fast in strength forming and high in final strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to a silicon-alumina cementitious material concrete and a preparation method thereof. Background Art

[0002] In the field of building materials, concrete, as the main material for infrastructure construction, has always been the focus of industry attention for its performance and cost. Traditional concrete mostly uses silicate cement as a cementing material, but the production cost of silicate cement is high and it imposes a heavy burden on the environment. Silica-alumina cementing materials are derived from industrial solid waste containing aluminosilicate glass. This type of cementing material not only provides similar performance to silicate cement-based cementing materials, but also reduces the consumption of cement clinker in the industry, reduces costs, absorbs solid waste, reduces environmental pressure, and achieves green and low-carbon development. It is therefore considered to be a low-carbon cementing material. Therefore, the research and development of silica-alumina cementing materials has become a hot topic in the current field of cement concrete science and technology.

[0003] However, the concrete strength of silicon-alumina cementitious materials is relatively low, and it is difficult to meet the demand for high-strength concrete in the use environment. Summary of the invention

[0004] Therefore, the object of the present invention is to provide a silicon-alumina cementitious material concrete which has both low cost and high strength.

[0005] Another object of the present invention is to provide a method for preparing the low-cost and high-strength silicon-alumina cementitious material concrete.

[0006] To this end, the present invention provides the following technical solutions:

[0007] A silicon-alumina cementitious material concrete comprises the following raw materials in parts by mass: 100-200 parts of red mud, 0-100 parts of fly ash, 0-100 parts of steel slag, 0-100 parts of lithium slag, 100-300 parts of slag powder, 0-100 parts of cement, 0-50 parts of gypsum, 150-200 parts of water, 40-50 parts of alkaline activator, 10-40 parts of steel fiber, 700-750 parts of sand, 900-1200 parts of crushed stone, and 1-5 parts of water reducer; the water reducer comprises a naphthalene-based high-efficiency water reducer and calcium lignin sulfonate; and the cement comprises silicate cement and / or silicate cement clinker.

[0008] Preferably, the following raw materials are included in parts by mass:

[0009] 100-145 parts of red mud, 20-60 parts of fly ash, 0-30 parts of steel slag, 0-30 parts of lithium slag, 190-250 parts of slag powder, 40-60 parts of cement, 5-20 parts of gypsum, 170-195 parts of water, 40-50 parts of alkaline activator, 15-30 parts of steel fiber, 700-750 parts of sand, 1000-1200 parts of crushed stone, and 3-5 parts of water reducer.

[0010] Further preferably, the following raw materials are included in parts by mass:

[0011] 125-135 parts of red mud, 40-60 parts of fly ash, 15-30 parts of steel slag, 15-30 parts of lithium slag, 210-235 parts of slag powder, 40-50 parts of cement, 10-20 parts of gypsum, 180-195 parts of water, 45-50 parts of alkaline activator, 20-30 parts of steel fiber, 720-750 parts of sand, 1120-1200 parts of crushed stone, and 4-5 parts of water reducer.

[0012] Preferably, the red mud is sintering red mud, which is solid waste discharged from the industrial production of alumina, and its components include oxides of calcium, iron, silicon, magnesium, and aluminum; the fly ash is Class C fly ash, which meets the requirements of GB / T 1596 "Fly ash used in cement and concrete", and has a moisture content of ≤1%; the steel slag is a block waste slag produced by steelmaking, and its components include oxides of calcium, iron, silicon, and magnesium; the lithium slag is a block waste slag discharged after leaching and washing after calcining spodumene and extracting the residue of lithium carbonate clinker by sulfuric acid method, and its components include oxides of calcium, iron, silicon, magnesium, and aluminum; the slag powder is water-quenched or air-cooled blast furnace slag powder; the silicate cement clinker and silicate cement both meet the requirements of GB / T 21372-2024 "Silicate Cement Clinker", and have a moisture content of ≤1%.

[0013] Preferably, the alkaline activator includes one or more of sodium carbonate, sodium hydroxide and sodium silicate; the purity of the sodium carbonate, sodium hydroxide and sodium silicate is independently ≥ 95%; the modulus of the sodium silicate is 1-3. Since the water contained in sodium carbonate, sodium hydroxide and sodium silicate is mainly crystal water and chemically bound water / hydroxyl group, the amount used in the raw material system accounts for a small proportion, and there is no need to specifically control the water content.

[0014] Preferably, the mass ratio of the naphthalene-based high-efficiency water reducer to calcium lignin sulfonate is (0.5-1.5): (0.5-1.5).

[0015] Preferably, the gypsum includes one or more of desulfurized gypsum, mirabilite gypsum, phosphogypsum and titanium gypsum; the water content of the gypsum is 8wt%-12wt%; the water content of the gypsum refers to the sum of the mass contents of physically adsorbed water and free water in the gypsum, excluding chemically bound water and crystallized water, wherein the water content can be determined by a drying method.

[0016] Preferably, the steel fibers include hook-end steel fibers and / or wavy steel fibers; the steel fibers are 3-5 cm long, 0.3-0.9 mm in diameter, and are made of carbon steel. Optionally, the surface of the steel fibers includes a copper coating.

[0017] Preferably, the particle size of the sand is 0.01-5 mm; the particle size of the gravel is 5-20 mm; and the sand includes machine-made sand.

[0018] Crushed stones with particle sizes of 5-20 mm are mixed together to form a continuous gradation.

[0019] Preferably, the water content of the silicon-alumina cementitious material concrete is ≤1%, and the water content refers to the sum of physically adsorbed water and free water, excluding chemically bound water and crystallized water. The water content can be measured by a drying method.

[0020] The present invention also provides a method for preparing the silicon-alumina cementitious material concrete, comprising the following steps:

[0021] (1) Pretreatment: drying and grinding the first component raw materials; the first component raw materials include red mud, steel slag, lithium slag and slag powder;

[0022] (2) Mixing: mixing the pretreated first component raw material with the second component to obtain a gelling material, and then mixing and stirring with the third component raw material to obtain a mixture;

[0023] The second component raw materials include fly ash, cement, gypsum and alkaline activator;

[0024] The third component raw materials include steel fiber, crushed stone and sand;

[0025] (3) Forming: adding water and a water reducing agent into the mixture and stirring evenly to obtain the silicon-alumina cementitious material concrete.

[0026] Preferably, in the above preparation method, at least one of the following conditions is met:

[0027] (1) After drying, the water content of the first component raw material is ≤3wt%;

[0028] (2) The goal of the grinding is: the residue on the sieve does not exceed 10 wt% when passing through an 80 μm square hole sieve;

[0029] The sieve residue refers to the percentage of powder that does not pass through the 80μm square hole sieve in the mass of the first component raw material after drying;

[0030] (3) The mixing and stirring time in step (2) is 1-3 min;

[0031] (4) The stirring time in step (3) is 2-4 min.

[0032] The technical solution of the present invention has the following advantages:

[0033] The present invention provides a silicon-aluminum cementitious material concrete, which comprises the following raw materials by weight: 100-200 parts of red mud, 0-100 parts of fly ash, 0-100 parts of steel slag, 0-100 parts of lithium slag, 100-300 parts of slag powder, 0-100 parts of cement, 0-50 parts of gypsum, 150-200 parts of water, 40-50 parts of alkaline activator, 10-40 parts of steel fiber, 700-750 parts of sand, 900-1200 parts of crushed stone, and 1-5 parts of water reducer; the water reducer comprises a naphthalene-based high-efficiency water reducer and calcium lignin sulfonate; the cement comprises silicate cement and / or silicate cement clinker. The present invention controls the proportion of red mud, slag powder, cement and alkaline activator, so that the compressive strength of the silicon-aluminum cementitious material concrete after curing for 1 day is greater than 30.0MPa, and the compressive strength after curing in water for 28 days is greater than 60.0MPa. It has the advantages of fast strength formation and high final strength.

[0034] In the present invention, red mud and alkaline activator work synergistically, red mud is alkaline raw material, and alkaline activator promotes activation of active components (aluminosilicate minerals) in red mud, dissolution-polymerization reaction occurs to form polymer gel, thereby improving the compressive strength of concrete.

[0035] Steel fibers can refine the microstructure of concrete and improve the stress distribution inside the concrete, so that the concrete can bear stress more evenly when under pressure, thereby improving the compressive strength of the concrete.

[0036] In the present invention, the water reducer includes a naphthalene-based high-efficiency water reducer and calcium lignin sulfonate. After the two are compounded and used, the strong dispersibility of the naphthalene-based water reducer and the slow setting and lubricating effect of calcium lignin sulfonate can effectively disperse cement particles, make the concrete mixture more uniform, and reduce water consumption. At the same time, the water retention is improved, water seepage is prevented, and it is effectively adapted to long-term transportation and high temperature environments. After compounding, the fluidity of the concrete can also be maintained, the appropriate viscosity is maintained, the operability and strength are improved, and the setting time is extended, which is suitable for large-volume construction and reduces the risk of early cracks. In addition, calcium lignin sulfonate has low cost, can reduce the overall additive dosage, and achieve economic benefits.

[0037] The silicon-alumina cementitious material concrete provided by the present invention can use up to 90% of solid waste (including red mud, steel slag, lithium slag, slag, fly ash and gypsum), making use of various solid wastes and having a significant environmental protection effect. In addition, by reasonably setting the amount of steel slag powder and lithium slag, part of the mineral powder (the cost of mineral powder is relatively high) is replaced, thus ensuring low cost and significantly improving the strength of the concrete.

[0038] The invention is scientifically designed and ingeniously conceived; the provided silicon-alumina cementitious material concrete has the advantages of low carbon and low energy consumption, and the hardened body exhibits good mechanical properties both in the early and late stages, thus broadening the application field.

[0039] The present invention also provides a method for preparing silicon-alumina cementitious material concrete, comprising the following steps: (1) pretreatment: drying and grinding the first component raw material; the first component raw material includes red mud, steel slag, lithium slag and slag powder; (2) mixing: mixing the first component raw material after the above pretreatment with the second component raw material to obtain a cementitious material, and then mixing and stirring with the third component raw material to obtain a mixture; the second component raw material includes fly ash, cement, gypsum and alkaline activator; the third component raw material includes steel fiber, crushed stone and sand; (3) molding: adding water and a water reducing agent to the mixture, stirring evenly, and obtaining the silicon-alumina cementitious material concrete. The preparation method of the silicon-alumina cementitious material concrete provided by the present invention is simple, and the problem of uneven feeding and mixing is avoided by a reasonable feeding sequence. The preparation process has low consumption and low CO2 emissions; it hardens quickly, has high strength, and has a wide range of applications; the preparation method is easy, low cost, energy-saving, low-carbon and environmentally friendly; from the technical, economic and environmental protection perspectives, the present invention will have significant social, economic and environmental benefits, is highly practical, and is suitable for popularization and use. DETAILED DESCRIPTION

[0040] Unless otherwise specified, the raw materials used in the examples are all known, commercially available chemical raw materials, specifically:

[0041] Red mud is sintered red mud, which is solid waste discharged from industrial production of alumina and is composed of oxides of calcium, iron, silicon, magnesium and aluminum;

[0042] The fly ash is Class C fly ash, which meets the requirements of GB / T 1596 "Fly ash used in cement and concrete", and has a moisture content of ≤1%;

[0043] Steel slag is a massive waste residue produced by steelmaking, composed of oxides of calcium, iron, silicon, and magnesium;

[0044] Lithium slag is the residue of lithium carbonate clinker extracted by sulfuric acid method after calcination of spodumene. It is discharged after leaching and washing. It is composed of oxides of calcium, iron, silicon, magnesium and aluminum and is in block form.

[0045] The slag powder is water-quenched or air-cooled blast furnace slag powder;

[0046] Both Portland cement clinker and Portland cement meet the requirements of GB / T 21372 "Portland cement clinker", with a moisture content of ≤1%;

[0047] The total amount of physically adsorbed water and free water in gypsum measured by the drying method accounts for 8-12% of the total water content of gypsum;

[0048] The purity of sodium carbonate, sodium hydroxide and sodium silicate is independently ≥95%, and the modulus of sodium silicate is 2; Example 1

[0049] This embodiment provides a silicon-alumina cementitious material concrete, including 145kg red mud, 30kg steel slag, 190kg slag powder, 40kg fly ash, 40kg Portland cement clinker, 5kg desulfurized gypsum, 180kg water, 50kg sodium carbonate, 4kg water reducer, 20kg steel fiber, 720kg machine-made sand, and 1120kg crushed stone;

[0050] The steel fiber is a copper-plated end hook type steel fiber;

[0051] The water reducer is composed of 2kg of naphthalene-based high-efficiency water reducer and 2kg of calcium lignin sulfonate;

[0052] Among them, the slag powder is water-quenched slag powder, the particle size of machine-made sand is 0.01-5mm, and the particle size of crushed stone is 5-20mm.

[0053] The preparation method of the above silicon-alumina cementitious material concrete is as follows:

[0054] (1) Pretreatment: drying and grinding the red mud, steel slag and slag powder (drying to a moisture content of ≤3 wt%; grinding to a powder with a sieve residue of no more than 10% on an 80 μm square hole sieve);

[0055] (2) Mixing: The pretreated raw materials are mixed with fly ash, silicate cement clinker, desulfurized gypsum and sodium carbonate to obtain a cementitious material, and then mixed with steel fiber, crushed stone and machine-made sand for 2 minutes to obtain a mixture;

[0056] (3) Forming: adding water and a water reducing agent into the mixture and stirring for 3 minutes to obtain the silicon-alumina cementitious concrete.

[0057] Embodiment 2:

[0058] This embodiment provides a silica-alumina cementitious material concrete, including: 145kg red mud, 30kg lithium slag, 190kg slag powder, 40kg fly ash, 40kg Portland cement clinker, 5kg desulfurized gypsum, 180kg water, 50kg sodium carbonate, 4kg water reducer, 20kg steel fiber, 720kg machine-made sand, and 1120kg crushed stone;

[0059] The steel fiber is a copper-plated end hook type steel fiber;

[0060] The water reducing agent is composed of 2kg of naphthalene-based high-efficiency water reducing agent and 2kg of calcium lignin sulfonate.

[0061] Among them, the slag powder is water-quenched slag powder, the particle size of machine-made sand is 0.01-5mm, and the particle size of crushed stone is 5-20mm.

[0062] The preparation method of the above silicon-alumina cementitious material concrete is as follows:

[0063] (1) Pretreatment: drying and grinding the red mud, lithium slag and slag powder (drying to a moisture content of ≤3 wt%; grinding to a powder with a sieve residue of no more than 10% on an 80 μm square hole sieve);

[0064] (2) Mixing: The pretreated raw materials are mixed with fly ash, silicate cement clinker, desulfurized gypsum and sodium carbonate to obtain a cementitious material, and then mixed with steel fiber, crushed stone and machine-made sand for 2 minutes to obtain a mixture;

[0065] (3) Forming: adding water and a water reducing agent into the mixture and stirring for 3 minutes to obtain the silicon-alumina cementitious concrete.

[0066] Example 3

[0067] This embodiment provides a silicon-alumina cementitious material concrete, including: 145kg red mud, 15kg steel slag, 15kg lithium slag, 190kg slag powder, 40kg fly ash, 40kg Portland cement clinker, 5kg desulfurized gypsum, 180kg water, 50kg sodium carbonate, 4kg water reducer, 20kg steel fiber, 720kg machine-made sand, and 1120kg crushed stone;

[0068] The steel fiber is a copper-plated end hook type steel fiber;

[0069] The water reducing agent is composed of 2kg of naphthalene-based high-efficiency water reducing agent and 2kg of calcium lignin sulfonate.

[0070] Among them, the slag powder is water-quenched slag powder, the particle size of machine-made sand is 0.01-5mm, and the particle size of crushed stone is 5-20mm.

[0071] The preparation method of the above silicon-alumina cementitious material concrete is as follows:

[0072] (1) Pretreatment: drying and grinding red mud, steel slag, lithium slag and slag powder (drying to a moisture content of ≤3 wt%; grinding to a powder with a sieve residue of no more than 10% on an 80 μm square hole sieve);

[0073] (2) Mixing: The pretreated raw materials are mixed with fly ash, silicate cement clinker, desulfurized gypsum and sodium carbonate to obtain a cementitious material, and then mixed with steel fiber, crushed stone and machine-made sand for 2 minutes to obtain a mixture;

[0074] (3) Forming: adding water and a water reducing agent into the mixture and stirring for 3 minutes to obtain the silicon-alumina cementitious concrete.

[0075] Example 4

[0076] This embodiment provides a silicon-alumina cementitious material concrete, including: 145kg red mud, 15kg steel slag, 15kg lithium slag, 190kg slag powder, 40kg fly ash, 40kg Portland cement clinker, 5kg desulfurized gypsum, 180kg water, 17.5kg sodium hydroxide, 27.5kg sodium silicate, 4kg water reducer, 20kg steel fiber, 720kg machine-made sand, and 1120kg crushed stone;

[0077] The steel fiber is a copper-plated end hook type steel fiber;

[0078] The water reducing agent is composed of 2kg of naphthalene-based high-efficiency water reducing agent and 2kg of calcium lignin sulfonate.

[0079] Among them, the slag powder is water-quenched slag powder, the particle size of machine-made sand is 0.01-5mm, and the particle size of crushed stone is 5-20mm.

[0080] The preparation method of the above silicon-alumina cementitious material concrete is as follows:

[0081] (1) Pretreatment: drying and grinding red mud, steel slag, lithium slag and slag powder (drying to a moisture content of ≤3 wt%; grinding to a powder with a sieve residue of no more than 10% on an 80 μm square hole sieve);

[0082] (2) Mixing: The pretreated raw materials are mixed with fly ash, silicate cement clinker, desulfurized gypsum, sodium hydroxide and sodium silicate to obtain a cementitious material, and then mixed with steel fiber, crushed stone and machine-made sand for 2 minutes to obtain a mixture;

[0083] (3) Forming: adding water and a water reducing agent into the mixture and stirring for 3 minutes to obtain the silicon-alumina cementitious concrete.

[0084] Example 5

[0085] 125kg red mud, 15kg steel slag, 15kg lithium slag, 210kg slag powder, 40kg fly ash, 40kg Portland cement clinker, 5kg desulfurized gypsum, 180kg water, 17.5kg sodium hydroxide, 27.5kg sodium silicate, 4kg water reducer, 20kg steel fiber, 720kg machine-made sand, 1120kg crushed stone;

[0086] The steel fiber is a copper-plated end hook type steel fiber;

[0087] The water reducing agent is composed of 2kg of naphthalene-based high-efficiency water reducing agent and 2kg of calcium lignin sulfonate.

[0088] Among them, the slag powder is water-quenched slag powder, the particle size of machine-made sand is 0.01-5mm, and the particle size of crushed stone is 5-20mm.

[0089] The preparation method of the above silicon-alumina cementitious material concrete is as follows:

[0090] (1) Pretreatment: drying and grinding red mud, steel slag, lithium slag and slag powder (drying to a moisture content of ≤3 wt%; grinding to a powder with a sieve residue of no more than 10% on an 80 μm square hole sieve);

[0091] (2) Mixing: The pretreated raw materials are mixed with fly ash, silicate cement clinker, desulfurized gypsum, sodium hydroxide and sodium silicate to obtain a cementitious material, and then mixed with steel fiber, crushed stone and machine-made sand for 2 minutes to obtain a mixture;

[0092] (3) Forming: adding water and a water reducing agent into the mixture and stirring for 3 minutes to obtain the silicon-alumina cementitious concrete.

[0093] Example 6

[0094] 100kg red mud, 15kg steel slag, 15kg lithium slag, 235kg slag powder, 40kg fly ash, 40kg Portland cement clinker, 5kg desulfurized gypsum, 180kg water, 17.5kg sodium hydroxide, 27.5kg sodium silicate, 4kg water reducer, 20kg steel fiber, 720kg machine-made sand, 1120kg crushed stone;

[0095] The steel fiber is a copper-plated end hook type steel fiber;

[0096] The water reducing agent is composed of 2kg of naphthalene-based high-efficiency water reducing agent and 2kg of calcium lignin sulfonate.

[0097] Among them, the slag powder is water-quenched slag powder, the particle size of machine-made sand is 0.01-5mm, and the particle size of crushed stone is 5-20mm.

[0098] The preparation method of the above silicon-alumina cementitious material concrete is as follows:

[0099] (1) Pretreatment: drying and grinding red mud, steel slag, lithium slag and slag powder (drying to a moisture content of ≤3 wt%; grinding to a powder with a sieve residue of no more than 10% on an 80 μm square hole sieve);

[0100] (2) Mixing: The pretreated raw materials are mixed with fly ash, silicate cement clinker, desulfurized gypsum, sodium hydroxide and sodium silicate to obtain a cementitious material, and then mixed with steel fiber, crushed stone and machine-made sand for 2 minutes to obtain a mixture;

[0101] (3) Forming: adding water and a water reducing agent into the mixture and stirring for 3 minutes to obtain the silicon-alumina cementitious concrete.

[0102] Example 7

[0103] 100kg red mud, 15kg steel slag, 15kg lithium slag, 235kg slag powder, 40kg fly ash, 40kg Portland cement clinker, 5kg desulfurized gypsum, 180kg water, 10kg sodium carbonate, 10kg sodium hydroxide, 20kg sodium silicate, 4kg water reducer, 20kg steel fiber, 720kg machine-made sand, 1120kg crushed stone;

[0104] The steel fiber is a copper-plated end hook type steel fiber;

[0105] The water reducing agent is composed of 2kg of naphthalene-based high-efficiency water reducing agent and 2kg of calcium lignin sulfonate.

[0106] Among them, the slag powder is water-quenched blast furnace slag powder, the particle size of machine-made sand is 0.01-5mm, and the particle size of crushed stone is 5-20mm.

[0107] The preparation method of the above silicon-alumina cementitious material concrete is as follows:

[0108] (1) Pretreatment: drying and grinding red mud, steel slag, lithium slag and slag powder (drying to a moisture content of ≤3 wt%; grinding to a powder with a sieve residue of no more than 10% on an 80 μm square hole sieve);

[0109] (2) Mixing: The pretreated raw materials are mixed with fly ash, silicate cement clinker, desulfurized gypsum, sodium carbonate, sodium hydroxide and sodium silicate to obtain a cementitious material, and then mixed with steel fiber, crushed stone and machine-made sand for 2 minutes to obtain a mixture;

[0110] (3) Forming: adding water and a water reducing agent into the mixture and stirring for 3 minutes to obtain the silicon-alumina cementitious concrete.

[0111] Example 8

[0112] This embodiment provides a silicon-alumina cementitious material concrete, including 100 kg of red mud, 15 kg of steel slag, 15 kg of lithium slag, 215 kg of slag powder, 60 kg of fly ash, 60 kg of Portland cement, 20 kg of phosphogypsum, 195 kg of water, 10 kg of sodium carbonate, 10 kg of sodium hydroxide, 20 kg of sodium silicate, 3 kg of water reducer, 15 kg of steel fiber, 700 kg of machine-made sand, and 1000 kg of crushed stone;

[0113] The steel fiber is a wavy steel fiber that has been copper-plated;

[0114] The water reducing agent is composed of 1.5 kg of naphthalene-based high-efficiency water reducing agent and 1.5 kg of calcium lignin sulfonate.

[0115] Among them, the slag powder is air-cooled blast furnace slag powder, the particle size of machine-made sand is 0.01-5mm, and the particle size of crushed stone is 5-20mm.

[0116] The preparation method of the above silicon-alumina cementitious material concrete is as follows:

[0117] (1) Pretreatment: drying and grinding the red mud, steel slag and slag powder (drying to a moisture content of ≤3 wt%; grinding to a powder with a sieve residue of no more than 10% on an 80 μm square hole sieve);

[0118] (2) Mixing: The pretreated raw materials are mixed with fly ash, silicate cement clinker, desulfurized gypsum and sodium carbonate to obtain a cementitious material, and then mixed with steel fiber, crushed stone and machine-made sand for 2 minutes to obtain a mixture;

[0119] (3) Forming: adding water and a water reducing agent into the mixture and stirring for 3 minutes to obtain the silicon-alumina cementitious concrete.

[0120] Example 9

[0121] This embodiment provides a silicon-alumina cementitious material concrete, including 135kg of red mud, 15kg of steel slag, 15kg of lithium slag, 250kg of slag powder, 20kg of fly ash, 50kg of Portland cement, 10kg of Glauber's salt gypsum, 170kg of water, 10kg of sodium carbonate, 10kg of sodium hydroxide, 20kg of sodium silicate, 5kg of water reducing agent, 30kg of steel fiber, 750kg of machine-made sand, and 1200kg of crushed stone;

[0122] The steel fiber is a wavy steel fiber that has been copper-plated;

[0123] The water reducing agent is composed of 2.5 kg of naphthalene-based high-efficiency water reducing agent and 2.5 kg of calcium lignin sulfonate.

[0124] Among them, the slag powder is air-cooled blast furnace slag powder, the particle size of machine-made sand is 0.01-5mm, and the particle size of crushed stone is 5-20mm.

[0125] The preparation method of the above silicon-alumina cementitious material concrete is as follows:

[0126] (1) Pretreatment: drying and grinding red mud, steel slag, lithium slag and slag powder (drying to a moisture content of ≤3 wt%; grinding to a powder with a sieve residue of no more than 10% on an 80 μm square hole sieve);

[0127] (2) Mixing: The pretreated raw materials are mixed with fly ash, silicate cement clinker, desulfurized gypsum, sodium carbonate, sodium hydroxide and sodium silicate to obtain a cementitious material, and then mixed with steel fiber, crushed stone and machine-made sand for 2 minutes to obtain a mixture;

[0128] (3) Forming: adding water and a water reducing agent into the mixture and stirring for 3 minutes to obtain the silicon-alumina cementitious concrete.

[0129] Comparative Example 1

[0130] This comparative example provides a silica-alumina cementitious material concrete, including 145kg red mud, 30kg steel slag, 190kg slag powder, 40kg fly ash, 40kg Portland cement clinker, 5kg desulfurized gypsum, 180kg water, 20kg sodium carbonate, 4kg water reducer, 20kg steel fiber, 720kg machine-made sand, and 1120kg crushed stone;

[0131] The steel fiber is a copper-plated end hook type steel fiber;

[0132] The water reducing agent is composed of 2kg of naphthalene-based high-efficiency water reducing agent and 2kg of calcium lignin sulfonate.

[0133] Among them, the slag powder is water-quenched blast furnace slag powder, the particle size of machine-made sand is 0.01-5mm, and the particle size of crushed stone is 5-20mm.

[0134] The preparation method of the above silicon-alumina cementitious material concrete is as follows:

[0135] (1) Pretreatment: drying and grinding the red mud, steel slag and slag powder (drying to a moisture content of ≤3 wt%; grinding to a powder with a sieve residue of no more than 10% on an 80 μm square hole sieve);

[0136] (2) Mixing: The pretreated raw materials are mixed with fly ash, silicate cement clinker, desulfurized gypsum and sodium carbonate to obtain a cementitious material, and then mixed with steel fiber, crushed stone and machine-made sand for 2 minutes to obtain a mixture;

[0137] (3) Forming: adding water and a water reducing agent into the mixture and stirring for 3 minutes to obtain the silicon-alumina cementitious concrete.

[0138] Comparative Example 2

[0139] This comparative example provides a silica-alumina cementitious material concrete, including 145kg red mud, 30kg steel slag, 190kg slag powder, 40kg fly ash, 40kg Portland cement clinker, 5kg desulfurized gypsum, 180kg water, 50kg sodium carbonate, 4kg water reducer, 720kg machine-made sand, and 1120kg crushed stone;

[0140] The water reducing agent is composed of 2kg of naphthalene-based high-efficiency water reducing agent and 2kg of calcium lignin sulfonate.

[0141] Among them, the slag powder is water-quenched blast furnace slag powder, the particle size of machine-made sand is 0.01-5mm, and the particle size of crushed stone is 5-20mm.

[0142] The preparation method of the above silicon-alumina cementitious material concrete is as follows:

[0143] (1) Pretreatment: drying and grinding the red mud, steel slag and slag powder (drying to a moisture content of ≤3 wt%; grinding to a powder with a sieve residue of no more than 10% on an 80 μm square hole sieve);

[0144] (2) Mixing: The pretreated raw materials are mixed with fly ash, silicate cement clinker, desulfurized gypsum and sodium carbonate to obtain a cementitious material, and then mixed with crushed stone and machine-made sand for 2 minutes to obtain a mixture;

[0145] (3) Forming: adding water and a water reducing agent into the mixture and stirring for 3 minutes to obtain the silicon-alumina cementitious concrete.

[0146] Comparative Example 3

[0147] This comparative example provides a silica-alumina cementitious material concrete, including 145kg red mud, 30kg steel slag, 190kg slag powder, 40kg fly ash, 40kg Portland cement clinker, 5kg desulfurized gypsum, 180kg water, 50kg sodium carbonate, 4kg polycarboxylate water reducer, 20kg steel fiber, 720kg machine-made sand, and 1120kg crushed stone;

[0148] The steel fiber is a copper-plated end hook type steel fiber;

[0149] Among them, the slag powder is water-quenched blast furnace slag powder, the particle size of machine-made sand is 0.01-5mm, and the particle size of crushed stone is 5-20mm.

[0150] The preparation method of the above silicon-alumina cementitious material concrete is as follows:

[0151] (1) Pretreatment: drying and grinding the red mud, steel slag and slag powder (drying to a moisture content of ≤3 wt%; grinding to a powder with a sieve residue of no more than 10% on an 80 μm square hole sieve);

[0152] (2) Mixing: The pretreated raw materials are mixed with fly ash, silicate cement clinker, desulfurized gypsum and sodium carbonate to obtain a cementitious material, and then mixed with steel fiber, crushed stone and machine-made sand for 2 minutes to obtain a mixture;

[0153] (3) Forming: adding water and polycarboxylic acid water-reducing agent into the mixture and stirring for 3 minutes to obtain the silicon-alumina cementitious concrete.

[0154] Test example:

[0155] The silicon-alumina cementitious material concrete obtained in Examples 1-9 was subjected to preparation, molding, curing and compressive strength testing of concrete specimens according to GB / T 50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete". The concrete blocks were demoulded after curing for 1 day in a curing box at 20°C±2°C and relative humidity not less than 95%, and the 1-day compressive strength was tested. The demoulded specimens were placed in water at 20°C±1°C for curing to 3d, 7d and 28d, and the compressive strength was tested. At the same time, the fluidity of the concrete was tested according to GB / T 50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures". The test results are shown in Table 1.

[0156] Table 1 Results of fluidity and compressive strength of silicon-alumina cementitious material concrete obtained in Examples 1-9

[0157]

[0158]

[0159] As can be seen from Table 1, the compressive strength of the silicon-alumina cementitious material concrete provided by the present invention after curing for 1 day is greater than 30.0 MPa, and the compressive strength after curing in water for 28 days is greater than 60.0 MPa. Compared with Examples 1, 2, 3, and 4, Examples 5 and 6 can significantly improve the strength of concrete by reasonably matching the multi-component red mud, steel slag, lithium slag, slag powder, silicate cement clinker, gypsum, and fly ash. Comparing Examples 6 and 7, it is found that different alkaline activators have different effects after compounding, and the activating effect is better after sodium carbonate, sodium hydroxide, and sodium silicate are reasonably matched.

[0160] It can be seen from the results of Comparative Example 1 that when the amount of alkaline activator changes, the final compressive strength of the silica-alumina cementitious material concrete will be significantly reduced. This is because the reduction in the amount of alkaline activator will directly affect the reaction process and product microstructure of the silica-alumina cementitious material, thereby significantly reducing the compressive strength of the concrete.

[0161] It can be seen from the results of Comparative Example 2 that the compressive strength of concrete can be significantly improved after adding steel fibers.

[0162] From the results of Comparative Example 3, it can be seen that the compounding of naphthalene-based high-efficiency water-reducing agent and calcium lignin sulfonate can significantly improve the fluidity of silicon-alumina cementitious concrete. This is because the compounding of naphthalene-based high-efficiency water-reducing agent and calcium lignin sulfonate can improve particle distribution and reduce water demand through synergistic effect, thereby improving fluidity.

[0163] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. A silicon-alumina cementitious material concrete, characterized in that: The raw materials include, by weight: 100-200 parts of red mud, 0-100 parts of fly ash, 0-100 parts of steel slag, 0-100 parts of lithium slag, 100-300 parts of slag powder, 0-100 parts of cement, 0-50 parts of gypsum, 150-200 parts of water, 40-50 parts of alkaline activator, 10-40 parts of steel fiber, 700-750 parts of sand, 900-1200 parts of crushed stone, and 1-5 parts of water reducer; The water reducer includes a naphthalene-based high-efficiency water reducer and calcium lignin sulfonate; The cement includes Portland cement and / or Portland cement clinker.

2. The silicon-alumina cementitious material concrete according to claim 1, characterized in that: In parts by mass, it includes the following raw materials: 100-145 parts of red mud, 20-60 parts of fly ash, 0-30 parts of steel slag, 0-30 parts of lithium slag, 190-250 parts of slag powder, 40-60 parts of cement, 5-20 parts of gypsum, 170-195 parts of water, 40-50 parts of alkaline activator, 15-30 parts of steel fiber, 700-750 parts of sand, 1000-1200 parts of crushed stone, and 3-5 parts of water reducer.

3. The silicon-alumina cementitious material concrete according to claim 1 or 2, characterized in that: In parts by mass, it includes the following raw materials: 125-135 parts of red mud, 40-60 parts of fly ash, 15-30 parts of steel slag, 15-30 parts of lithium slag, 210-235 parts of slag powder, 40-50 parts of cement, 10-20 parts of gypsum, 180-195 parts of water, 45-50 parts of alkaline activator, 20-30 parts of steel fiber, 720-750 parts of sand, 1120-1200 parts of crushed stone, and 4-5 parts of water reducer.

4. The silicon-alumina cementitious material concrete according to any one of claims 1 to 3, characterized in that: The alkaline activator includes one or more of sodium carbonate, sodium hydroxide and sodium silicate; Preferably, the modulus of the sodium silicate is 1-3.

5. The silicon-alumina cementitious material concrete according to any one of claims 1 to 4, characterized in that: The mass ratio of the naphthalene-based high-efficiency water reducer to calcium lignin sulfonate is (0.5-1.5): (0.5-1.5).

6. The silicon-alumina cementitious material concrete according to any one of claims 1 to 5, characterized in that: The gypsum includes one or more of desulfurized gypsum, mirabilite gypsum, phosphogypsum and titanium gypsum; Preferably, the water content of the gypsum is 8wt%-12wt%.

7. The silicon-alumina cementitious material concrete according to any one of claims 1 to 6, characterized in that: The steel fibers include end hook type steel fibers and / or corrugated steel fibers; Optionally, the surface of the steel fiber includes a copper coating.

8. The silicon-alumina cementitious material concrete according to any one of claims 1 to 7, characterized in that: The particle size of the sand is 0.01-5 mm; the particle size of the crushed stone is 5-20 mm; Preferably, the sand comprises manufactured sand.

9. The method for preparing silicon-alumina cementitious material concrete according to any one of claims 1 to 8, characterized in that: The steps include: (1) Pretreatment: drying and grinding the first component raw materials; the first component raw materials include red mud, steel slag, lithium slag and slag powder; (2) Mixing: Mixing the pretreated first component raw material with the second component raw material to obtain a gelling material, and then mixing and stirring with the third component raw material to obtain a mixture; The second component raw materials include fly ash, cement, gypsum and alkaline activator; The third component raw materials include steel fiber, crushed stone and sand; (3) Forming: adding water and a water reducing agent into the mixture and stirring evenly to obtain the silicon-alumina cementitious material concrete.

10. The method for preparing silicon-alumina cementitious material concrete according to claim 9, characterized in that: At least one of the following conditions is met: (1) After drying, the water content of the first component raw material is ≤3wt%; (2) The goal of the grinding is: the residue on the sieve does not exceed 10 wt% when passing through an 80 μm square hole sieve; (3) The mixing and stirring time in step (2) is 1-3 min; (4) The stirring time in step (3) is 2-4 min.